5PSQ-175 Cytotoxic T lymphocyte antigen 4 mutations on T reg and abatacept: a paediatric case report. (14th March 2021) - Traina, S; Scaldaferri, M; Caiazza, E; Cattel, F
Abstract : Background and importance: The lymphoproliferative autoimmune syndrome caused by cytotoxic T lymphocyte antigen 4 (CTLA-4) insufficiency is characterised by immune dysregulation, haploinsufficiency and multiorgan disorders. This condition is classified as a rare disease and no drugs are yet registered for treatment. Abatacept, an antirheumatic agent that prevents T lymphocyte activation, was proposed. Aim and objectives: To report the clinical record of a 15-year-old female patient with autoimmune disorders. Material and methods: In 2015, the patient showed Gilbert pityriasis rosea with significant and diffused lymphoadenopathy, and levothyroxine was prescribed for her hypothyroidism. In July 2018, the patient had chronic urticaria and angio-oedema with a low antihistamine response. In April 2019, she showed persistent fever, asthenia and splenomegaly, associated with multiple lymphoadenopathies, compatible with a lymphoproliferative autoimmune syndrome. 1 Functional tests evidenced a significant reduction in CTLA-4 expression on T reg lymphocytes. In November 2019, omalizumab was started instead of levocetirizine with benefit. In February 2020, clinicians from the paediatric infections unit proposed to the internal pharmaceutical committee the use of intravenous abatacept as off-label chronic treatment to manage autoimmune disorders related to CTLA-4 mutations. As the patient was suffering from a rare disease, the pharmacists suggested compassionate use of the drug, as for the DM 07/09/2017, also due to the elevated cost of the therapy chosen. Results: The use of abatacept has shown a positive outcome to date (after seven doses), with regression in all lymphoadenopathy sites observed. Moreover, because the patient is successfully responding to intravenous administration in hospital, the ethical committee also approved the switch to the subcutaneous form which can be administered at home. Conclusion and relevance: Abatacept use in CTLA-4 mutations on T reg may represent a valid chance of positive disease regression. However, eight months of observation of a single patient is not sufficient and more studies and applications are required. Moreover, a literature research and evaluation led the pharmacist to suggest compassionate use to guarantee the patient's therapy and to optimise drug governance, not affecting hospital costs. References and/or acknowledgements: Schwab, et al . J Allergy Clin Immunol 2018;142 :1932–46. Conflict of interest: No conflict of interest